Availability and Utilization of Instructional Materials in Teaching Geography in Secondary Schools - Dhakal, Keshav Raj (The Third Pole: Journal of Geography Education, 2018)
This study examines the availability and utilization of instructional materials in geography teaching in community secondary schools in Kathmandu district. There are altogether sixteen community secondary schools offering geography as an optional subject. Out of sixteen secondary schools offering geography as an optional subject eight schools are selected for the study on the basis of random sampling. The sample for this study comprised of one hundred seventy four students from selected secondary schools. The survey and observation are used for primary data collection. The data are analyzed using percentage. The results reveal that printed and graphic instructional materials for teaching geography in secondary schools are available and their utilization is of high extent while audio, visual and audio-visual instructional materials for teaching geography are not available sufficiently and they are used less often in the classrooms for teaching geography. The local materials are rarely utilized in schools by the teachers. All stakeholders in education must rise to the challenges of making instructional materials are available and utilized in secondary schools. The Third Pole: Journal of Geography Vol. 17: 51-58, 2017